Iron indices and hemogram in renal anemia and the improvement with Tribulus terrestris green-formulated silver nanoparticles applied on rat model - Wu Xiujuan; Shi Jingyan; Dai Yangping; Tang Weiqi; Cao Huijun; Chen Jieyu (Open Chemistry, 2024)
The recent research was done to assess the hematological and biochemical disorders in nephrotoxicity induced by gentamicin (100 mg/kg) in Wistar rats. The green-formulated silver nanoparticles (AgNPs) by Tribulus terrestris leaf were analyzed by XRD, energy-dispersive X-ray spectrometer, and field emission scanning electron microscopy. The shape of the recent nanoparticles was spherical in size of 48 nm. In the in vivo, the classical and novel kidney injury parameters were used to assess the nephroprotective properties of AgNPs in animal model. Gentamicin decreased significantly (P ≤ 0.01) the value of PCV, concentration of HB, and count of RBC. The value of serum iron, erythropoietin, Cr, and urea raised in the gentamicin group. Leucogram revealed thrombocytopenia, granulocytosis, and leukocytosis. AgNPs improved the iron, erythropoietin, thrombocytes, leukogram, and erythrogram. The levels of creatinine, urea, GGT, ALT, AST, and ALP significantly reduced and albumin and total protein increased in group treated with AgNPs. Also, AgNPs significantly raised the anti-inflammatory cytokines, i.e., IL3, TGFβ, IL10, IL5, and IL4, and decreased the pro-inflammatory cytokines, i.e., TNFα, IL18, IL12, IL6, and IL1. These findings may offer AgNPs as a nephroprotective agent that could be a suitable therapeutic supplement in blood disorders conditions.